Buildings with environmental quality management: Part 4: A path to the future NZEB. (July 2019) - Romanska-Zapala, Anna; Bomberg, Mark; Yarbrough, David W
The previous part of this article starts 100 years ago, at the time of the humble beginnings of building science, and brings us to the current stage of the net zero energy buildings (NZEB). We see how, over the years, knowledge from the observed failures of buildings has accumulated to become the basis for current building science. The strong interactions between energy efficiency, moisture management, and indoor environment and the need for their simultaneous analysis led to the concept of environmental assessment. More than 40 years of experience with passive houses (the first 10 were built in Canada in 1977) in process that would collect those developments into the mainstream of NZEB technology permits extrapolation to the future. As the first priority, we see a need for a fundamental change in the approach to NZEB—instead of improving the separate pieces of the puzzle before assembling them, we need first to establish the conceptual design of the whole system. Only after determination of the basic requirements for each subsystem and each assembly may materials that would fulfill the specific requirements of this assembly be selected. In this design process, the actual climate and socio-economic conditions (including construction cost) vary, so we must deal with a set of design principles rather than a description of a specific construction technology. A guiding set of considerations is presented below to establish a system of environmental quality management (EQM).